1998
DOI: 10.1001/archpsyc.55.11.973
|View full text |Cite
|
Sign up to set email alerts
|

Familial Transmission of Substance Use Disorders

Abstract: Elevation in risk of this magnitude places a family history of drug disorder as one of the most potent risk factors for the development of drug disorders. These results suggest that there may be risk factors that are specific to particular classes of drugs as well as risk factors that underlie substance disorders in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
424
3
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 707 publications
(464 citation statements)
references
References 53 publications
30
424
3
7
Order By: Relevance
“…In other words, such vulnerability -whatever the cause, genetic and/ or environmental life events -may reflect a potential or already constituted state of reward system allostasis. Such vulnerability may be a drug-specific phenomenon in that a large component of the heritability is specific for a particular drug (Bierut et al 1998;Merikangas et al 1998).…”
Section: Vulnerability To Addiction and Allostasis: Genetic Contributmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, such vulnerability -whatever the cause, genetic and/ or environmental life events -may reflect a potential or already constituted state of reward system allostasis. Such vulnerability may be a drug-specific phenomenon in that a large component of the heritability is specific for a particular drug (Bierut et al 1998;Merikangas et al 1998).…”
Section: Vulnerability To Addiction and Allostasis: Genetic Contributmentioning
confidence: 99%
“…In other words, such vulnerability -whatever the cause, genetic and/ or environmental life events -may reflect a potential or already constituted state of reward system allostasis. Such vulnerability may be a drug-specific phenomenon in that a large component of the heritability is specific for a particular drug (Bierut et al 1998;Merikangas et al 1998).Substantial evidence exists for an important genetic contribution to the vulnerability to develop alcoholism and tobacco addiction. Twin studies with adoption have provided strong evidence for an important genetic influence on the risk of becoming an alcoholic in both men and women (Heath et al 1997a).…”
mentioning
confidence: 99%
“…In addition to the adaptation that accompanies alcohol abuse, genetic background can unquestionably contribute to the susceptibility of an individual for alcoholism (Cloninger et al 1981;Cloninger 1987;Dick et al 2002;Heath et al 1997;Merikangas 1990;Merikangas et al 1998;Reich et al 1998). To account for this susceptibility, it is presumed that the adaptive consequences of repeated chronic alcohol exposures and stresses are facilitated in individuals with a genetic vulnerability for alcohol abuse.…”
Section: Stress During Withdrawal From Multiple Alcohol Exposures Incmentioning
confidence: 99%
“…Family, twin and adoption studies suggest that genetic factors are implicated in vulnerability of substance abuse (Merikangas et al, 1998;Kendler, 2001;Kendler et al, 2000;Tsuang et al, 2001). The genome-scanning study of poly-substance abuse vulnerability demonstrated that the brain-derived neurotrophic factor (BDNF) gene might be one of the strong candidate genes to drug abuse (Uhl et al, 2001).…”
Section: Introductionmentioning
confidence: 99%